Drimane Sesquiterpenoids Noncompetitively Inhibit Human α4β2 Nicotinic Acetylcholine Receptors with Higher Potency Compared to Human α3β4 and α7 Subtypes - Arias, Hugo Rubén (2018)
The drimane sesquiterpenoids drimenin, cinnamolide, dendocarbin A, and polygodial were purified from the Canelo tree (Drimys winteri) and chemically characterized by spectroscopic methods. The pharmacological activity of these natural compounds were determined on hα4β2, hα3β4, and hα7 nicotinic acetylcholine receptors (AChRs) by Ca2+ influx measurements. The results established that drimane sesquiterpenoids inhibit AChRs with the following selectivity: hα4β2 > hα3β4 > hα7. In the case of hα4β2 AChRs, the following potency rank order was determined (IC50's in μM): drimenin (0.97 ± 0.35) > cinnamolide (1.57 ± 0.36) > polygodial (62.5 ± 19.9) dendocarbin A (no activity). To determine putative structural features underlying the differences in inhibitory potency at hα4β2 AChRs, additional structure-activity relationship and molecular docking experiments were performed. The Ca2+ influx and structural results supported a noncompetitive mechanism of inhibition, where drimenin interacted with luminal and nonluminal (TMD-β2 intrasubunit) sites. The structure-activity relationship results, i.e., the lower the ligand polarity, the higher the inhibitory potency, supported the nonluminal interaction. Ligand binding to both sites might inhibit the hα4β2 AChR by a cooperative mechanism, as shown experimentally (nH > 1). Drimenin could be used as a molecular scaffold for the development of more potent inhibitors with higher selectivity for the hα4β2 AChR.